Mobile laboratories as an alternative to conventional remote laboratories - Saliah-Hassane, Hamadou (2018)
Remote laboratories have been playing an important role on the improvement of flexibility and the extent of practical activities in teaching and learning activities in engineering and technology. However, the current remote laboratories model does not consider dynamic scenarios including collaboration, peer-to-peer labs and mobile labs. This paper presents a set of tools for creating collaborative online mobile laboratories that allow students to develop their own labs and share them with classmates and teachers. The approach used is compatible with the machine and network configurations that the target user has in schools and at home, and provides the retrieval of information for learning evaluation.